Usefulness and acceptability of a standardised orientation and mobility training for partially-sighted older adults using an identification cane - Ballemans Judith; Zijlstra GA; van Rens Ger HMB; Schouten Jan SAG; Kempen Gertrudis IJM (BMC, 2012)
Abstract Background Orientation and mobility (O&M) training in using an identification (ID) cane is provided to partially-sighted older adults to facilitate independent functioning and participation in the community. Recently, a protocolised standardised O&M-training in the use of the ID cane was developed in The Netherlands. The purpose of this study is to assess the usefulness and acceptability of both the standardised training and the regular training for participants and O&M-trainers in a randomised controlled trial (NCT00946062). Methods The standardised O&M-training consists of two structured face-to-face sessions and one telephone follow-up, in which, in addition to the regular training, self-management and behavioural change techniques are applied. Questionnaires and interviews were used to collect data on the training's usefulness, e.g. the population reached, self-reported benefits or achievements, and acceptability, e.g. the performance of the intervention according to protocol and participants' exposure to and engagement in the training. Results Data was collected from 29 O&M-trainers and 68 participants. Regarding the self-reported benefits, outcomes were comparable for the standardised training and the regular training according the trainers and participants e.g., about 85% of the participants in both groups experienced benefits of the cane and about 70% gained confidence in their capabilities. Participants were actively involved in the standardised training. Nearly 40% of the participants in the standardised training group was not exposed to the training according to protocol regarding the number of sessions scheduled and several intervention elements, such as action planning and contracting. Conclusions The standardised and regular O&M-training showed to be useful and mostly acceptable for the partially-sighted older adults and trainers. Yet, a concern is the deviation from the protocol of the standardised O&M-training by the O&M-trainers regarding distinguishing elements such as action planning. Overall, participants appreciated both trainings and reported benefit.